Literature Review on the Implementation of the Independent Curriculum in Elementary Schools: Opportunities and Challenges for Classroom Teachers - Desi Ratna (Ludi Litterarri, 2024)
The Independent Curriculum is a form of educational reform that aims to address the challenges of 21st-century learning through a flexible approach, differentiated learning, and strengthening student character. This study aims to in-depth examine the opportunities and challenges of implementing the Independent Curriculum in elementary schools through a qualitative literature review. Data sources were obtained from various scientific publications and relevant policy documents spanning the past five years. The study results indicate that the Independent Curriculum provides space for classroom teachers to develop contextual and participatory learning. However, several challenges remain in its implementation, including teachers' limited understanding of curriculum principles, gaps in pedagogical capacity, and a lack of ongoing technical assistance. This literature review also found that successful implementation is largely determined by the synergy between teacher capacity, principal leadership, and local context-based policy support. Therefore, strategies are needed to strengthen the elementary education ecosystem that supports the transformation of teachers' roles as facilitators of independent and reflective learning. This research provides conceptual and practical contributions to the development of educational policies and the improvement of the quality of pedagogical practices at the elementary school level.